To Cause Harm and to be Harmed by Others: New Perspectives on Alcohol's Harms to Others - Abdu K. Seid; Ulrike Grittner; Thomas K. Greenfield; Kim Bloomfield (SAGE Publishing, 2015)
Objective To examine how sociodemographic factors and alcohol consumption are related to a four-way typology of causing harm to others and/or being harmed by othersș and one's own drinking. Data and Methods Data from the 2011 Danish national survey ( n = 2,569) were analyzed with multinomial logistic regression. Results Younger age and heavy drinking were significant correlates of both causing harm and being harmed. Women and better educated respondents were more likely to report negative effects on relationship and family from another's drinking. Better educated respondents had higher risks for work, financial, or injury harms from another's drinking. Mean alcohol consumption and risky single occasion drinking were related to both causing harm and being harmed from one's own drinking. Conclusions Drinking variables were the strongest correlates of causing harm and being harmed. Efforts to reduce risky drinking may also help reduce exposures to collateral harm.